Potent Anti‐Inflammatory and Pro‐Resolving Effects of Anabasum in a Human Model of Self‐Resolving Acute Inflammation. Issue 4 (30th January 2018) - Motwani, Madhur P.; Bennett, Frances; Norris, Paul C.; Maini, Alexander A.; George, Marc J.; Newson, Justine; Henderson, Alice; Hobbs, Adrian J.; Tepper, Mark; White, Barbara; Serhan, Charles N.; MacAllister, Raymond; et al.
Abstract : Anabasum is a synthetic analog of Δ 8 ‐tetrahydrocannabinol (THC)‐11‐oic acid that in preclinical models of experimental inflammation exerts potent anti‐inflammatory actions with minimal central nervous system (CNS) cannabimimetic activity. Here we used a novel model of acute inflammation driven by i.d. UV‐killed E. coli in healthy humans and found that anabasum (5 mg) exerted a potent anti‐inflammatory effect equivalent to that of prednisolone in terms of inhibiting neutrophil infiltration, the hallmark of acute inflammation. These effects arose from the inhibition of the neutrophil chemoattractant LTB4, while the inhibition of antiphagocytic prostanoids (PGE2, TxB2, and PGF2 α) resulted in enhanced clearance of inflammatory stimulus from the injected site. Anabasum at the higher dose of 20 mg possessed the additional properties of triggering the biosynthesis of specialized pro‐resolving lipid mediators including LXA4, LXB4, RvD1, and RvD3. Collectively, we demonstrate for the first time a striking anti‐inflammatory and pro‐resolution effects of a synthetic analog of THC in healthy humans.